DAMPAK TEKNOLOGI INFORMASI TERHADAP PERUBAHAN STRUKTUR KOTA DAN SISTEM TRANSPORTASI - Nandi, Nandi (Indonesia University of Education, 2010)
Currently, wireless communications brings a new dimension in human interaction. The process of this interaction will be more conducted by human in the future without depending on the location of comunicating. It is still difficult to predict how quickly humans can adapt to this technology. As well as the effectiveness of the use of SMS (short messages service) which is a new phenomenon, need some time to expand knowledge about how to use them. Thus, a wireless telecommunications can bring a big influence to human behavior. Advances in technology will shape and continue to shape the economic and physical development of urban areas. New telecommunications technology and urban economic development, can changing roles and patterns of physical development. Many big cities lose its function as the headquarters or manufacturing centers because of the intensive information activities such as customer service centers and research and development laboratory. Furthermore, information technology which is progress very rapidly forming a new challenge in finance, health and education. It became the basis of the needs in urban areas also play a role in trade and culture in urban areas (Moss, 1988). This paper will try to present the impact caused by developments information technology to change the urban structure and urban transportation systems.